Studi Stilistika Al-Quran: Kajian Teoritis dan Praktis Pada Surat Al-Ikhlas - Lukman Fajariyah (Alfaz (Arabic Literatures for Academic Zealots), 2020)
The study of linguistics has experienced quite dynamic developments in the contemporary era. Linguistics is the main tool in dissecting or studying texts. One representation of the branch of linguistics that has attracted the attention of scholars or language researchers is stylistics. Stylistics is one of the linguistic disciplines that are quite comprehensive or interdisciplinary (macro linguistics). This is because stylistics includes elements of other linguistic disciplines such as semantics, phonology, syntax, and morphology. The stylistic study, which was originally used to discuss literary texts, is currently developing and is included in the study of the text of the holy Koran. This study seeks to explore the stylistics of the Koran in surah al-Ikhlas. The aim is to find out and reveal the use of language and textual linguistic aesthetics in surah al-Ikhlas. The research method used is qualitative-descriptive. The findings in this study show that the stylistics in the surah al-Ikhlas include several al-mustawayat, namely; al-mustawa al-nahwi (syntactic level), al-mustawa al-sarfi (morphological level), al-mustawa al-sauti (phonological level), al-mustawa al-dalali (semantic level), and al-mustawa al- tashwiri (imagery level). Through some of this al-mustawayat we can get meaning and deep understanding in the form of the oneness or unity of Allah, with all the power implied in the meaning of the surah al-Ikhlas can refute the negative stigmas of the polytheists and can also increase the firmness of a Muslim's faith.